Indonesian News Website Accessibility Evaluation Based on WCAG 2.2 for Visually Impaired User - Desak Putu Putri Dharmayanti; Putu Yudia Pratiwi; I Gusti Ayu Agung Diatri Indradewi (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Web accessibility is essential to ensure equal access to online information for all users, including individuals with visual impairments. Despite the increasing reliance on online news platforms, the accessibility status of Indonesian news websites remains underexplored, particularly with respect to the latest Web Content Accessibility Guidelines (WCAG) 2.2. This study evaluates the accessibility compliance of the three most visited Indonesian news websites, namely Detik.com, Kompas.com, and Tribunnews.com, from the perspective of users with visual impairments. The evaluation was conducted using WCAG 2.2 as the accessibility standard, the Website Accessibility Conformance Evaluation Methodology (WCAG-EM) as the evaluation method, and three automated accessibility evaluation tools: WAVE, axe DevTools, and Siteimprove Accessibility Checker. The findings indicate that all evaluated websites still contain accessibility barriers that may hinder access for visually impaired users. Keyboard accessibility violations were identified as the most dominant issue, followed by violations related to non-text content and color contrast. The results also reveal that homepage pages generally exhibit more accessibility issues than article pages due to their higher complexity and larger number of interactive and advertisement-related components. Among the evaluated websites, Tribunnews.com demonstrated the best overall accessibility performance, followed by Kompas.com and Detik.com. Furthermore, advertisement and promotional components were found to contribute substantially to the identified accessibility issues. These findings highlight the need for Indonesian news website providers to prioritize accessibility throughout the design and development process to promote more inclusive access to online news content.